Закономірності впливу низькоінтенсивного електромагнітного випромінювання на біологічні системи - Garkusha, O. M.; Mazurenko, R. V.; Makhno, S. M.; Gorbyk, P. P. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
The paper summarizes the experimental results obtained in recent years in the physical and biological research, the influence of low-intensity electromagnetic radiation of millimeter range on biological objects of various levels of the organization was examinet. It is shown that the response of the objects studied (yeast, blood, and extracellular enzymes) to the effects of prolonged exposure is frequency-selective.